Antibacterial and Antibiofilm Activity of Methanolic Plant Extracts against Nosocomial Microorganisms - Sánchez, Eduardo; Rivas Morales, Catalina; Castillo, Sandra; Leos Rivas, Catalina; García Becerra, Ledy Elizabeth; Ortiz Martínez, David Mizael (2016)
Biofilm is a complex microbial community highly resistant to antimicrobials.The formation of biofilms in biotic and abiotic surfaces is associated with high rates of morbidity and mortality in hospitalized patients. New alternatives for controlling infections have been proposed focusing on the therapeutic properties of medicinal plants and their antimicrobial effects. In the present study the antimicrobial and antibiofilm activities of 8 methanolic plant extracts were evaluated against clinical isolated microorganisms. Preliminary screening by diffusion well assay showed the antimicrobial activity of Prosopis laevigata, Opuntia ficus-indica, and Gutierrezia microcephala. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined ranging from 0.7 to >15 mg/mL. The specific biofilm formation index (SBF) was evaluated before and after the addition of plant extracts (MBC × 0.75). Opuntia ficus-indica caused the major reduction on SBF in dose-dependent manner. Cytotoxic activity of plant extracts was determined using brine shrimp lethality test (Artemia salina L.). Lethal Dose concentration (LD50 values) of the plant extracts was calculated. LD50 values for P. laevigata and G. microcephalawere 141.6 and 323.3